THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL CAPABILITY ON FINANCIAL WELLBEING OF SMEs IN MALAYSIA - Mas Azira Mohamed; Sellywati Mohd Faizal; Nahariah Jaffar, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This research aimed at finding out the effect of FL and FC on the FWB of SMEs in Malaysia. This study specifically focused on the FL framework developed by the OECD, which consist of three key components: The following constructs are chosen: financial behavior (FB), financial knowledge (FK), and financial attitude (FA). Also, the study also aimed at assessing the moderating effect of FC in this relationship. Participants for this study were SMEs in Malaysia and data was collected using a survey with 231 respondents. In line with the objectives and hypotheses, the data was analyzed using partial least square (PLS) – structural equation modeling. The results of the study supported the postulated FL and FC as having a significant effect on the FWB of SMEs. Therefore, it can be concluded that this study offered a strong reasoning that the link between FWB and FL was Moderated by FC. This research provides a novel way of considering the factors that affect the FWB of SMEs and relies on the Stimulus-Organism-Response theory. Thus, this study seeks to develop a holistic framework that captures the complex relationships between the factors that affect the FWB of SMEs. From the above literature, the researchers will be in a better position to comprehend and understand the concept of SMEs’ FWB, especially in Malaysia. Thus, subsequent similar studies on SMEs’ FWB may be conducted, and the difference found could be applicable across various industries or areas. The foregoing thus depicts the importance of SMEs in every economy as they are indeed the backbone. Nevertheless, few research pay attention to their FWB, particularly in Malaysia.